Progressivism Civic Education in Indonesia: An Ontological, Epistemological, and Axiological Framework for Students’ Adaptive Nationalism - Rini Setiyowati; Rr Siti Murtiningsih; Armaidy Armawi (Journal Evaluation in Education (JEE), 2026)
Purpose of the study: This study examines how civic education based on the philosophy of progressivism can strengthen adaptive nationalism in the digital era. Civic education is outlined within a philosophical framework of ontology, epistemology, and axiology and transformed into pedagogical principles. Methodology: This research is a philosophical hermeneutic study based on document analysis. Academic and policy texts are selected purposively, interpreted interactively through a hermeneutical circle to clarify the ontological, epistemological, and axiological foundations of progressive civic education, and then derived into pedagogical principles. The validity of the interpretation is maintained through data triangulation. Main Findings: Progressive civic education, ontologically, frames students as Pancasila-grounded citizens operating in global contexts. Epistemologically, it prioritizes experiential learning, with project- and problem-based approaches cultivating critical reasoning and media literacy. Axiologically, it promotes pluralistic, constitutional, ethically grounded critical patriotism, guiding civic participation toward responsible engagement, democratic accountability, and respect for diversity in both offline and digital public spheres. Novelty/Originality of this study: This research offers a philosophical framework for progressive civic education by outlining its ontology, epistemology, and axiology. Its main novelty is the integrative concept of adaptive nationalism, which unites the principles of Pancasila in state governance, public participation, and critical discourse.